The Effect of Using Reciprocal Teaching on Improving College Students' Achievement in Reading Comprehension - Maysaa Raheed Abdul-Majeed (College of Education for Women, 2019)
Reciprocal Teaching is an interactive method that is used to improve reading comprehension. Using this teaching strategy, teachers and students take turns leading discussions regarding sections of text using the four strategies: predicting, questioning, clarifying and summarizing. This study is an attempt to investigate the effect of using reciprocal teaching on improving female college students' achievement in reading comprehension. To fulfill the aim of the study, the researcher has adopted two null hypotheses: first, there is no significant difference between the achievement of students' who practice the reciprocal teaching technique and that of students who do not practice it. Second, there is no statistically significant difference between the experimental group students' achievement in the pre and posttests of reading comprehension. To achieve the aim of the study, a four-week experiment was conducted using pretest-posttest nonequivalent groups design. Two groups of thirty students each were selected from the population of first year students/college of education for women-department of English. One group was selected as the experimental group (namely section C D) and other group was selected as the control group (namely section E F). Both students of the experimental and control groups were exposed to pre and posttests. Using the t-test for two independent samples, it is found that there is a statistically significant difference in favour of the experimental group. This indicates that reciprocal teaching technique is more effective than the presentation practice production teaching or the Lecture Method teaching. At the end of the research paper, conclusions, recommendations and suggestions for further studies are put forward.